2016
DOI: 10.1021/acs.joc.6b01261
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ring Size and Migratory Groups on [1,n] Suprafacial Shift Reactions. Confirmation of Aromatic and Antiaromatic Transition-State Character by Ring-Current Analysis

Abstract: Suprafacial sigmatropic shift reactions of 5-substituted cyclopentadienes, 3-substituted cyclopropenes, and 7-substituted cycloheptatrienes have been studied computationally at the MP2/6-31+G* level for structures and energetics, and using the ipsocentric method at the CHF/6-31G** level to calculate current-density maps. The hydrogen shifts in cyclopentadienes have a diatropic ring currents indicating aromatic, cyclopentadienide anion character. This result stands in contrast to the fluorine shift in 5-fluoroc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 52 publications
1
16
0
Order By: Relevance
“…Further, the [1,5]-shifts in cyclic alkenes like cyclopentadiene, cyclopropene, and cycloheptatriene have also been experimentally and theoretically explored. [21][22][23][24] Not only hydrogen but also halogens are good migrating groups and are known to undergo [1,5]-sigmatropic shifts. 7b, 10,19,[25][26][27][28][29][30][31] To the best of our knowledge, there are no reports that compare the rate of migratory aptitude and stereochemical preference (supra/antara) of halogens during [1,5]-shift in 1,3-pentadiene.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, the [1,5]-shifts in cyclic alkenes like cyclopentadiene, cyclopropene, and cycloheptatriene have also been experimentally and theoretically explored. [21][22][23][24] Not only hydrogen but also halogens are good migrating groups and are known to undergo [1,5]-sigmatropic shifts. 7b, 10,19,[25][26][27][28][29][30][31] To the best of our knowledge, there are no reports that compare the rate of migratory aptitude and stereochemical preference (supra/antara) of halogens during [1,5]-shift in 1,3-pentadiene.…”
Section: Introductionmentioning
confidence: 99%
“…The [1,5]‐hydrogen shift in 1,3‐pentadiene is found to occur via concerted suprafacial fashion. Further, the [1,5]‐shifts in cyclic alkenes like cyclopentadiene, cyclopropene, and cycloheptatriene have also been experimentally and theoretically explored . Not only hydrogen but also halogens are good migrating groups and are known to undergo [1,5]‐sigmatropic shifts 7b, 10, 19, 25–31.…”
Section: Introductionmentioning
confidence: 99%
“…[11] Note that these studies focused on the geminally disubstituted compounds, although for monosubstituted cyclopentadienes, the relative stability, suprafacial shift reactions, and intrinsic acidity have been investigated. [12] However, the influence of substituents on hyperconjugative aromaticity in monosubstituted compounds remains uncertain. In addition, when one electronegative and one electropositive substituent are simultaneously considered, which one will dominate?…”
mentioning
confidence: 99%
“…[9] Recently,F owler and co-workerss howed that electropositive migratory groups( e.g., CH 3 and SiMe 3 )c ould reduce the [1,5]-shift activation energies, whereas the electronegative migratory groups (e.g.,F )l ed to larger activation energies as ar esult of the aromatic and antiaromatic character of the TSs. [10] Owing to many fascinating and ever-increasing manifestations, hyperconjugative aromaticity [11] and [1,5]-shifts [12] in cyclopentadienes have received much attention.I n2 016, the first hyperconjugative aromatic heterocycles containing transition-metal substituents werer eportede xperimentally and computationally. [13] Recently,w e also predicted the most aromatic pyrrolium and cyclopentadiene rings through hyperconjugation [14] caused by transitionmetal substituents.…”
Section: Introductionmentioning
confidence: 99%
“…In 2010, Yáñez and co‐workers proposed that the activation barriers of the [1,5]‐shift could be regulated by migratory groups (e.g., CH 3 , SiH 3 , and GeH 3 ), owing to hyperconjugative aromaticity . Recently, Fowler and co‐workers showed that electropositive migratory groups (e.g., CH 3 and SiMe 3 ) could reduce the [1,5]‐shift activation energies, whereas the electronegative migratory groups (e.g., F) led to larger activation energies as a result of the aromatic and antiaromatic character of the TSs . Owing to many fascinating and ever‐increasing manifestations, hyperconjugative aromaticity and [1,5]‐shifts in cyclopentadienes have received much attention.…”
Section: Introductionmentioning
confidence: 99%